THE INFLUENCE OF DRONE LARVAE HOMOGENATE ON PROOXIDANT-ANTIOXIDANT HOMEOSTASIS IN GILTS IN THE PERIOD OF PUBERTY - Shostya, A.M.; Yemets, Ya. M.; Kuzmenko, L.M.; Moroz, O. G.; Stupar, I.I. (Scientific Progress & Innovations, 2019)
In the conditions of industrial technology, the manifestation of normal physiological functions causing the processes of herd reproduction has changed significantly, manifesting in a weakly expressed sexual cycle and late onset of economic maturity, reducing the resistance of the organism, which is affected by stress fac-tors and systemic hypodynamia. This requires the development of reproductive biotechnologies based on using natural stimulants of animal origin, one of which is drone larvae homogenate (DLH). The aim of the study was to determine the effect of drone larvae homogenate on pro-oxidant-antioxidant homeostasis in gilts during puberty. Gilts of the Large White breed were used in the experiment, analogues by age and live weight, which were fed with drone larvae homogenate. It has been established that during the puberty period the intensification of peroxidation processes in gilts’ blood takes place, which is manifested by increasing the content of diene conjugates on the 180th and 210th days of development by 63.6% and 44.1% respectively. This is confirmed by a significant increase in the number of secondary peroxidation products − TBA-active complexes in the specified periods of their development, by 38.7 % and 30.6 % respectively. It has been revealed that during the period of gilts’ sexual maturation, the antioxidant protection system is the most labile from 6 to 8 months of age, where the variability of PAG components is significant due to the in-creased activity of superoxide dismutase (p<0.01) and catalase (p<0.05 ) and also the amount of restored glutathione. Additional feeding with DLH contributes to probable slowing down peroxidation processes in the blood, which is confirmed by a lower content of diene conjugates (p<0.05-0.01) and TBA-active com-plexes (p<0.01-0.001). It has been found that feeding DLH to pigs significantly influences the formation of reproductive function during puberty: the period of the first sexual cycle is reduced by 4 days, the duration of sexual cycles and time of the third estrus beginning are optimized by 7 days, prolificacy - 0.5 heads of pig-lets and weight of litter at birth and weaning are optimized as well.